농업용수관리 일원화 방안 연구 - 김홍상 (한국농촌경제연구원, 2005)
The agricultural water management system (AWMS) in Korea has been guided by two disparate managing subjects: central government-sponsored Korea Agricultural and Rural Infrastructure Corporation (KARICO) and grassroot Irrigation Clubs (ICs) with the support from municipalities. With due respect to the historical contexts, however, the current disconnected system has been criticized for its deficiency in supporting agro-producers' demands and securing valuable natural environment and built irrigation facilities in rural areas. That is mainly because about 150 municipalities have shown common lack in financial resources, inter-regional cooperation and technological expertise integral to the proper management of irrigation facilities and arable land under their auspices. Based on the backgrounds, this study aims to suggest a practical way to overcome various defects in the current AWMS in Korea: the merging of the municipal management into an integrated management guided by KARICO. Main suggestions are as follows: First, the study identified problems in the current system, especially in the municipal management and concluded that it was the most practical solution to the problems to institutionalize an integrated system run by KARICO. The proposed integrated AWMS is expected to enhance the quality of service delivery in the old municipal management and to contribute to the specialization of the agricultural water management in Korea. Second, in spite of KARICO field workers' preference to the partial merging of municipalities' facilities, the merging needs to be done in a bulk; given restrictions on the budget, substantive improvement in the management of the merged facilities is to be attained on an incremental basis. Third, it is essential to have farmers participate in the new system, individually and organizationally. Although specific measures will vary according to socio-political situations, educational measures need to be devised to eventually get farmers' labor, management knowledge, or monetary share. In addition, labor contracts in the current AWMS in KARICO need to be made more flexible. Researchers: Hong-Sang Kim and Jae-Mahn Shim E-mail address: hskim@krei.re.kr